The effect of motor learning and fatigue on preactivation of the lower extremity muscles during different jumps - Kamelska, A. M.; Kot, B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The first step in identifying risk factors for injuries is to characterize the myoelectric activity of different muscles after ground contact, especially when fatigue is a limiting factor. This study aimed at recording the myoelectric activity of calf muscles after ground contact during different types of jumps and investigating the effect of motor learning and fatigue on muscle preactivation. METHODS: Twenty four male students aged 24.3±1.2 years old performed three different motor activities: A) jump from a box with counter landing (JCL) on 30x30 cm plate; B) drop jump with bounce drop jump (BDJ); and C) BDJ followed by a jump on 51-cm step. The surface electromyography was used to examine the following muscles: m. tibialis anterior (TA), m. gastrocnemius medialis, m. gastrocnemius lateralis, and m. soleus (SO). The measurements were taken during different jumps before and after motor learning and fatigue stimulus. RESULTS: There were significant differences in preactivation for TA between JCL and BDJ followed by a jump under the influence of fatigue (P<0.05). The differences were observed also during BDJ between non-fatigued and fatigued conditions. There was a statistically significant difference for GL between BDJ pre- and postmovement motor learning and BDJ pre- and postfatigue influence. CONCLUSIONS: Current results indicate that myoelectric activity of muscles during motor activities is different, and the effect of motor learning and fatigue was shown. Thus, it could be important in the injury prevention in sport.